STRATEGI DIGITALISASI UMKM: PENDAMPINGAN DAN IMPLEMENTASI DI KAMPUNG BATIK PUNGSARI, SRAGEN - Khristiana, Yenni; Santosa, Jarot; Utomo, Agus; Imron Pahlawi, Lukman Ahmad; Susilowati, Eko Meiningsih (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
MSMEs have a strategic role in the Indonesian economy, but still face various obstacles in the adoption of digitalization, especially in rural areas. This community service program aims to help digitize and expand the marketing of MSMEs in Pungsari Village, Plupuh District, Sragen Regency. The methods used include business digitization training, social media-based marketing assistance. This activity involves local MSME players and collaborates with PT Mikrobisnis Digital Sejahtera in the INAmikro program. The results of this program show that 60% of participants experienced an increase in turnover of 20-50%, and 65% of MSMEs managed to reach markets outside the region after implementing digital marketing strategies through Instagram, Facebook, and TikTok Shop. In addition, 85% of participants successfully created business accounts and optimized e-commerce features to expand customer reach. However, some challenges remain, such as limited digital literacy and effective content management. Therefore, further assistance and continuous monitoring are needed so that MSMEs can optimally utilize digital technology and be highly competitive in the digital economy era.